Giardia muris and Giardia duodenalis groups: ultrastructural differences between the trophozoites - Sogayar, Maria Inês L. [UNESP]; Gregório, Elisa Aparecida [UNESP] (Instituto de Medicina Tropical, 1989)
Neste trabalho foi analisada, através de Microscopia Eletrônica de Transmissão, a morfologia de trofozoitos de Giardia muris obtidos de hamsters, ratos peridomiciliares e camundongos, bem como de trofozoitos de Giardia duodenalis obtidos de hamsters e ratos peridomiciliares. Basicamente a ultraestrutura dos trofozoitos estudados foi semelhante. Foram observadas, no entanto, diferenças na morfologia da franja ventro-lateral dos trofozoitos de Giardia muris quando comparados com os de Giardia duodenalis, diferenças estas relacionadas ao tamanho, arranjo das lâminas marginais e presença de lamela osmiofílica.

Trophozoites of the Giardia muris group from hamsters, domestic rats and mice and of the Giardia duodenalis group from hamsters and domestic rats were examined by transmission electron microscopy. The basic ultrastructure of the trophozoites was similar. Differences were shown in the morphology of the ventrolateral flange of the trophozoites of Giardia muris and Giardia duodenalis groups. Marginal plates are less developed in the species of the Giardia duodenalis group. In this group, the distal extremity of the lateral flange is short and thick and the marginal plate does not penetrate into the distal extremity of the flange. In the Giardia muris group, the ventro-lateral flange is well developed and narrow and the marginal plate penetrates the distal extremity of the flange. The osmiophilic lamella, which accompanies the dorsal surface of the marginal plate is seen only in the Giardia muris group.
Giardia muris e Giardia duodenalis: diferenças ultraestruturais entre trofozoitos
Keywords: Giardia muris; Giardia duodenalis; Trophozoite; Ultrastructure